أثر التسويق الوردي في ارضاء الزبائن "دراسة عينة من مستخدمات منتجات التجميل لوريال (l'oréal) بالمسيلة_الجزائر_" - ميمون, نبيلة (Université de M'sila, 2018)
يتناول البحث موضوع من أهم المواضيع الحديثة في مجال التسويق، ألا وهو التسويق الوردي أو التسويق النسائي، والهدف من ذلك ابراز أثر التسويق الوردي في ارضاء الزبائن، وقد تم تقديم دراسة تطبيقية على عينة من مستخدمات منتجات التجميل لوريال (L'ORÉAL) بالمسيلة_الجزائر_، وقد قدرت العينة ب 125 امرأة. توصلنا من خلال البحث إلى وجود أثر غير دال للتسويق الوردي في ارضاء الزبائن، وذلك بسبب الأثر الدال احصائيا لعناصر المزيج التسويقي الوردي وهي المنتج الوردي والتوزيع الوردي في ارضاء الزبائن، أما التسعير الوردي والترويج الوردي فوجدنا أثرهما غير دال. summary: The research deals with one of the most important modern marketing, namely, pink marketing or women marketing. The aim is to highlight the effect of pink marketing on customer satisfaction. A practical study was conducted on a sample of L'ORÉAL cosmetics users in msila_ Algeria, The sample was estimated at 125 women. In the research we found that there is a non-marketing effect of pink marketing on the satisfaction of customers, because of the significant effect of the elements of pink marketing mix, the pink product and the pink distribution in the satisfaction of customers. Pink pricing and pink promotion found their effect is not statistically significant. Résumé: L’étude porte sur les sujets modernes les plus importants dans le domaine du marketing, à savoir le marketing rose ou le marketing féminin, dans le but de souligner l’effet du marketing rose sur la satisfaction de la clientèle. L'échantillon a été estimé à 125 femmes. Nous avons constaté que le marketing rose avait un effet non marketing sur la satisfaction des clients en raison de l’effet significatif des éléments de mix marketing rose, à savoir le produit rose et la distribution rose de la satisfaction client.
Keywords: الكلمات المفتاحية: التسويق الوردي،المنتج الوردي، السعر الوردي، التوزيع الوردي، الترويج الوردي، رضا الزبائن ; Keywords: pink marketing, pink product, pink price, pink distribution, pink promotion, customer satisfaction ; Mots-clés: marketing rose, produit rose, prix rose, distribution rose, promotion rose, satisfaction de la clientèle